The Elephant to Hollywood : The Autobiography - Caine, Michael (London Hodder & Stoughton Ltd., 2010)
Film legend and British icon Sir Michael Caine's major new autobiography. When Maurice Micklewhite was born in poverty near Elephant and Castle, nobody would have guessed that he'd end up a Hollywood film star. Michael Caine looks back on the astonishing journey he's made.
Include Illustrations and Index.
An English Autobiography.
Keywords: Motion picture actors and actresses -- Great Britain -- Caine, Michael